2004
DOI: 10.1016/s1525-1578(10)60538-7
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Mutation in the Primer Binding Region of the Amelogenin Gene Can Interfere with Gender Identification

Abstract: PCR amplification of part of the X-Y homologous amelogenin gene with a single primer pair has been used as a sex identification test because it generates different length products from the X and Y chromosomes. Using a commercially available kit that contains amelogenin primers, we report a single phenotypically normal Caucasian male out of 327 males tested to date that failed to show an X chromosomespecific PCR product. Using alternative amelogenin primers external to but encompassing the initial amplicon, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 9 publications
3
31
1
1
Order By: Relevance
“…Previous reports revealed failure of the amelogenin sex determination tests in some cases. Deletions or mutations in primer binding sites for X and Y chromosome amelogenin homologs occur in human populations and may lead to gender misidentification (11)(12)(13). To avoid this potential problem, we have developed a gender-identification system adapted for the analysis of degraded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports revealed failure of the amelogenin sex determination tests in some cases. Deletions or mutations in primer binding sites for X and Y chromosome amelogenin homologs occur in human populations and may lead to gender misidentification (11)(12)(13). To avoid this potential problem, we have developed a gender-identification system adapted for the analysis of degraded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…The genes encoding amelogenin and zinc finger proteins are routinely used for sex determination [22][23][24]. For STRbased determination of sex, 6 bp deletion polymorphisms located in intron 3 of the amelogenin gene, on the X chromosome, can generally be detected by size differences [23].…”
Section: Discussionmentioning
confidence: 99%
“…For STRbased determination of sex, 6 bp deletion polymorphisms located in intron 3 of the amelogenin gene, on the X chromosome, can generally be detected by size differences [23]. Previous studies have performed SNP-based sex determination by examining differences in the sequences of the amelogenin genes located on the X and Y chromosomes [9].…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available kits for genotyping short tandem repeats (STRs) usually contain the AMEL primers and have been widely used in DNA databasing, forensic casework, prenatal diagnoses, and transplantation monitoring. Several studies have reported mutations in the X or Y homologue of the AMEL gene, which could cause amplification failure of AMELX or AMELY and result in incorrect sex identification [3][4][5][6][7][8][9][10][11][12]. In the Chinese population, however, some scattered cases with AMEL gene mutations have been reported [5][6][7], although no systematic analysis of the frequency data based on large samples has been done.…”
Section: Introductionmentioning
confidence: 99%